Preparation and application of a nanoscale Co2C / PTFE composite photothermal material

By preparing nano-scale cobalt carbide nano-carbide particles in a mixed reducing atmosphere of CO2/H2, nano-scale cobalt carbide particles and composited with PTFE films, the problem of preparation of cobalt carbide nanomaterials and low efficiency of photothermal water evaporation systems in the prior art is solved. The problem of efficient photothermal conversion and water evaporation performance is achieved.

CN116285173BActive Publication Date: 2025-02-25SHANDONG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310102082.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-25
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently prepare cobalt carbide nanomaterials with good dispersion, and the traditional photothermal water evaporation system is relatively low.

Method used

Nano-scale cobalt carbide particles were prepared by carbonizing in a mixed reducing atmosphere of CO2/H2 using the cobalt-based Prussian blue analog Co-PBA as the precursor, and their suspension was suctioned to a polytetrafluoroethylene (PTFE) film On the above, a Co2C/PTFE film composite material is formed to construct an interface photothermal water evaporation system.

Benefits of technology

It achieves efficient photothermal conversion and water evaporation performance, which is better than the widely reported Mxenes/carbon-based materials, has the potential for industrial production and reduces energy waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285173B_ABST
    Figure CN116285173B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of nanomaterial preparation, and specifically relates to the preparation and application of a nanoscale Co2C / PTFE composite photothermal material. The method of the present invention is simple, and the conditions are mild. A cobalt-based Prussian blue analog (Co‑PBA) is used as a precursor, and carbonization is performed in a mixed reducing atmosphere of CO2 / H2 to prepare nanoscale cobalt carbide particles, and the cobalt carbide suspension is filtered onto a polytetrafluoroethylene film to obtain a Co2C / PTFE film composite material. With the excellent light absorption and photothermal conversion capabilities of the cobalt carbide material, and the interfacial water evaporation system constructed after being composited with the PTFE film, light can be efficiently utilized to convert light energy into heat energy, thereby showing a photothermal interfacial water evaporation performance that is superior to the currently widely reported Mxenes / carbon-based materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation, and specifically relates to a cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material, a preparation method thereof, and photothermal water evaporation application. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Transition metal carbides (TMCs) are a type of interstitial alloys composed of transition metal elements and carbon elements. They can be simply understood as the periodic insertion of carbon atoms into the atomic lattice of transition metals, which causes the metal lattice to expand and the distance between metal atoms to change, thereby affecting the d-band electron distribution of metal atoms. Due to the introduction of carbon atoms, the electronic properties of TMCs can be adjusted by hybridization between the s and p orbitals of alloying carbon and the d orbitals of the host metal, so that TMCs exhibit surface properties similar to those of platinum group noble metals. As early as 1973, Levy et al. discovered that tungsten carbide exhibited catalytic behavior similar to that of the noble metal Pt in catalysis. Subsequently, WC and its neighboring family TMCs materials have successively entered the public eye. At present, due to their unique electronic structure and surface properties, some common transition metal carbides, such as Mo 2 C,Ti 3 C 2 ,Nb 3 C 2 ,VC,Fe 5 C 2 It has been widely reported to be used in various fields.

[0004] Cobalt carbide (Co 2 C) As a potential replacement material for Pt group noble metals, it has shown good application potential in energy storage, seawater desalination, catalytic hydrogen production, Fischer-Tropsch reaction, electromagnetic interference shielding, conductive films and other fields due to its good hydrophilicity, electrical conductivity and photothermal conversion ability.

[0005] In addition, cobalt carbide-based materials themselves have good stability and excellent mechanical properties and physical and chemical properties. They are also widely used in catalysis, energy, biology, and medicine.

[0006] At present, the methods for preparing cobalt carbide nanomaterials that have been reported are as follows: (1) high temperature wet chemical method, (2) programmed temperature carbonization reduction method, (3) laser etching method, (4) spinning method, and (5) ball milling method. However, the above methods and technologies have the problems of harsh experimental conditions, low yield, easy introduction of impurities and difficult separation of products, and low practicality, which seriously hinders the development of the basic material properties and multiple application potential of cobalt carbide. There is no report on the controllable large-scale production of single-phase cobalt carbide. In addition, due to the easy aggregation and agglomeration of carbide nanoparticles, the utilization rate of the unit cobalt carbide component in practical applications is low. How to better prepare cobalt carbide-based nanomaterials with good dispersion is also a research focus for the full application of cobalt carbide materials in the future.

[0007] With the development of human society and the continuous improvement of industrialization level, the global water shortage caused by water pollution has become one of the serious problems that modern society urgently needs to solve in order to alleviate the shortage of fresh water resources. By 2025, three-quarters of the world's population will face water shortages, and more than half of the countries will fall into the dilemma of fresh water shortage. As a green energy source, solar energy is expected to achieve zero-energy consumption and low-cost seawater desalination. It has attracted widespread attention by converting solar energy into thermal energy and purifying water through the evaporation process. The traditional solar evaporation system adopts bottom heating and overall heating. Due to the need to heat the entire water body, a large amount of heat loss occurs, resulting in low evaporation efficiency. In recent years, interfacial water evaporation can achieve more efficient water evaporation efficiency by placing photothermal conversion materials on the surface of seawater and selectively heating a thin layer of water at the vapor-liquid interface to produce steam. Based on the above principles, the construction of efficient interfacial water evaporation solar evaporator systems and photothermal conversion materials has become the focus of research for many scholars at home and abroad. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a cobalt carbide nanoparticle-loaded polytetrafluoroethylene film photothermal material and its preparation method and water evaporation application. The method of the present invention is simple, mild and flexible. It uses cobalt-based Prussian blue analogue (Co-PBA) as a precursor and 2 / H 2 The cobalt carbide suspension was filtered onto a polytetrafluoroethylene (PTFE) film to obtain Co 2 C / PTFE film composite material. With the excellent light absorption and photothermal conversion capabilities of cobalt carbide materials, and the interfacial water evaporation system constructed after being composited with PTFE film, light can be efficiently utilized to convert light energy into heat energy, thus showing better photothermal interfacial water evaporation performance than the currently widely reported Mxenes / carbon-based materials.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] The first aspect of the present invention provides a nanoscale Co 2 The preparation method of C / PTFE composite photothermal material comprises:

[0011] Using cobalt-based Prussian blue analog Co-PBA as a precursor, in the presence of CO 2 / H 2 Carbonizing in a mixed reducing atmosphere at 230-330° C. for 5-15 h to obtain nano-scale cobalt carbide particles;

[0012] dispersing the nano-scale cobalt carbide particles in a solvent to form a nano-scale cobalt carbide particle suspension;

[0013] The nanoscale cobalt carbide particle suspension is filtered onto a polytetrafluoroethylene (PTFE) film to obtain Co 2 C / PTFE film composite material;

[0014] Among them, H 2 and CO 2 The volume ratio is 1:1~1.5;

[0015] The temperature of carbonization roasting is 230-330°C and the time is 5-15h.

[0016] Based on this, the present invention proposes a method for preparing a cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material with good dispersibility. The preparation method is simple and flexible, the conditions are mild, and the cobalt carbide nanoparticles have good dispersibility. The method can be suitable for the industrial preparation of cobalt carbide-based film materials, and plays an important guiding role in promoting the industrial application of cobalt carbide nanomaterials.

[0017] The second aspect of the present invention provides a cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material prepared by the above method.

[0018] The third aspect of the present invention provides the application of the above-mentioned cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material in photothermal water evaporation. Cobalt carbide is used as a substitute for precious metals and is compounded with carbon-based fiber materials to construct an interfacial photothermal water evaporation system to achieve efficient photothermal conversion, which is of great significance to the equivalent reduction of current photothermal conversion materials.

[0019] Beneficial Effects of the Invention

[0020] (1) The preparation method provided by the present invention has a simple process, mild conditions, low cost, and is suitable for nanoscale Co 2 Industrial production of C / PTFE film composites;

[0021] (2) The present invention uses Co 2C / PTFE film composite material is used as the interface photothermal conversion material, replacing the traditional precious metal-based materials, and achieving high efficiency of photothermal water evaporation under light conditions, greatly avoiding the energy waste caused by the traditional photothermal water evaporation system;

[0022] (3) Compared with the widely reported Mxenes / carbon-based thin film materials, Co 2 C / PTFE film composite material achieves better photothermal conversion capability and interfacial water evaporation performance than Mxenes / PTFE, which is helpful to realize industrial production.

[0023] (4) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0025] Figure 1 is an X-ray diffraction (XRD) pattern of the cobalt carbide nanoparticles obtained in Example 1 of the present invention;

[0026] Figure 2 is a transmission electron microscope (TEM) image of the cobalt carbide nanoparticles and Mxenes obtained in Example 1 of the present invention;

[0027] Figure 3 is a surface scanning energy spectrum (Mapping) of the cobalt carbide nanoparticles obtained in Example 1 of the present invention;

[0028] Figure 4 The Co obtained in Example 1 of the present invention 2 High-resolution images of C / PTFE film composite materials;

[0029] Figure 5 The Co obtained in Example 1 of the present invention 2 Comparison of the photothermal conversion capabilities of C powder and Mxenes powder;

[0030] Figure 6 YesCo 2 Photothermal interface water evaporation efficiency diagram of C / PTFE film composite and Mxenes / PTFE film composite. DETAILED DESCRIPTION

[0031] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0032] A first typical embodiment of the present invention, a Co 2 The preparation method of the C / PTFE film composite material comprises the following steps:

[0033] S1. Dissolving a cobalt salt and potassium cobalt cyanide in deionized water to obtain a cobalt salt solution and a potassium cobalt cyanide solution, respectively, mixing the cobalt salt solution and the potassium cobalt cyanide solution, standing, centrifuging, washing, drying, and grinding to obtain Co-PBA;

[0034] S2. Carbonizing and calcining Co-PBA in a reducing atmosphere to obtain cobalt carbide nanomaterials.

[0035] S3, filtering the cobalt carbide nanoparticle suspension onto the PTFE membrane to obtain Co 2 C / PTFE film composite material.

[0036] In one or more examples of this implementation mode, the cobalt salt is one or more of cobalt nitrate, cobalt acetate, and cobalt chloride.

[0037] In one or more examples of this embodiment, the molar ratio of the cobalt salt to potassium cobalt cyanide is 0.5-3:1.

[0038] In one or more examples of this implementation, the mixing process is to slowly drop the cobalt salt solution into the potassium cobalt cyanide solution at a uniform speed under room temperature and stirring.

[0039] In one or more examples of this embodiment, the standing time is 0-96h, and the standing temperature is room temperature;

[0040] The centrifugal speed is 5000-10000 rpm, and the centrifugal time is 5-10 min;

[0041] The cleaning reagents were deionized water and ethanol;

[0042] The drying temperature is 50-150°C and the drying time is 2-48h.

[0043] In one or more embodiments of this embodiment, the reducing atmosphere is H 2 and CO 2 Mixed gas, H 2 and CO 2 The volume ratio is 1:1~1.5.

[0044] In one or more examples of this embodiment, the temperature of the carbonization roasting is 230-330° C., and the time is 5-15 hours.

[0045] In one or more examples of this implementation mode, the concentration of the cobalt carbide suspension in the filtration process is 0.1-1.0 mg / ml, the ultrasonic treatment is 1-5 hours, and the filtration time is 5-60 minutes.

[0046] A second typical embodiment of the present invention is a Co 2 C / PTFE film composite material, through the above Co 2 The preparation method of C / PTFE film composite is obtained.

[0047] A third typical embodiment of the present invention, the above-mentioned Co 2 Application of C / PTFE film composites in photothermal water evaporation.

[0048] In one or more examples of this implementation, the conditions for testing the performance of the solar water evaporation are as follows: the light source is a xenon lamp, the wavelength is simulated sunlight AM 1.5, and the light intensity is 0.1 W·cm -2 The mass of filtered cobalt carbide and MXenes control was 20 mg, the irradiation time was 60 min, and the reaction device was an interfacial water evaporator.

[0049] In one or more examples of this embodiment, the light-to-heat conversion capacity test conditions are: the light source is a xenon lamp, the wavelength is simulated sunlight AM 1.5, and the light intensity is 0.2 W·cm -2 The mass of cobalt carbide powder and MXenes control was 20 mg, and the irradiation time was 15 min.

[0050] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0051] Example 1

[0052] (1) Weigh 0.75 mmol of cobalt acetate and 0.5 mmol of potassium cobalt cyanide to prepare a solution, add 200 mL of deionized water to each solution, and stir to fully dissolve them.

[0053] (2) Add the prepared cobalt acetate solution dropwise into the potassium cobalt cyanide solution and continue stirring for 15 minutes after the addition.

[0054] (3) The obtained pink suspension was allowed to stand at room temperature for 48 h, and the obtained Co-PBA was centrifuged at 7500 rpm for 4 min, washed twice with deionized water, then washed twice with anhydrous ethanol, dried at 80°C for 12 h, and then ground.

[0055] (4) Place the ground Co-PBA in H 2 :CO 2 =1:1 mixed reducing atmosphere, carbonization calcination is carried out at 300°C, the heat preservation time is 5h, and after carbonization is completed, the particles are taken out to obtain cobalt carbide nanoparticles, which are then ground.

[0056] (5) Disperse 20 mg of cobalt carbide in 100 mL of deionized water and ultrasonicate for 2 h. Filter the cobalt carbide suspension onto a PTFE membrane at room temperature for 10 min.

[0057] like Figure 1 As shown, it can be seen that the diffraction peak position of this material is consistent with the standard Co 2 The main peak positions of C (PDF#72-1369) coincide with each other, indicating that Co was successfully prepared. 2 C nanoparticle material. Morphology Figure 2 As shown in the figure, it can be seen that the cobalt carbide particles are spherical and the size distribution is between 10-50nm; Mxenes present a single-layer or few-layer sheet structure. Figure 3 As shown in the Mapping diagram, it can be seen that carbon and cobalt elements are evenly distributed in the cobalt carbide nanomaterial. Figure 4 As shown, after filtration, it can be seen that the cobalt carbide nanoparticles are evenly filtered onto the PTFE film.

[0058] Example 2

[0059] (1) Weigh 0.75 mmol of cobalt acetate and 0.5 mmol of potassium cobalt cyanide to prepare a solution, add 200 mL of deionized water to each solution, and stir to fully dissolve them.

[0060] (2) Add the prepared cobalt acetate solution dropwise into the potassium cobalt cyanide solution and continue stirring for 15 minutes after the addition.

[0061] (3) The obtained pink suspension was allowed to stand at room temperature for 48 h, and the obtained Co-PBA was centrifuged at 7500 rpm for 4 min, washed twice with deionized water, then washed twice with anhydrous ethanol, dried at 80°C for 12 h, and then ground.

[0062] (4) Place the ground Co-PBA in H 2 :CO 2 =1:1 mixed reducing atmosphere, carbonization calcination is carried out at 300°C, the heat preservation time is 10h, and after carbonization is completed, the particles are taken out to obtain cobalt carbide nanoparticles, which are then ground.

[0063] (5) Disperse 20 mg of cobalt carbide in 100 mL of deionized water and ultrasonicate for 5 h. Filter the cobalt carbide suspension onto a PTFE membrane at room temperature for 10 min.

[0064] Example 3

[0065] ((1) Weigh 0.75 mmol of cobalt acetate and 0.5 mmol of potassium cobalt cyanide to prepare a solution, add 200 mL of deionized water to each solution, and stir to fully dissolve them.

[0066] (2) Add the prepared cobalt acetate solution dropwise into the potassium cobalt cyanide solution and continue stirring for 15 minutes after the addition.

[0067] (3) The obtained pink suspension was allowed to stand at room temperature for 48 h, and the obtained Co-PBA was centrifuged at 7500 rpm for 4 min, washed twice with deionized water, then washed twice with anhydrous ethanol, dried at 80°C for 12 h, and then ground.

[0068] (4) Place the ground Co-PBA in H 2 :CO 2 =1:1 mixed reducing atmosphere, carbonization calcination is carried out at 250°C, the heat preservation time is 10h, and after carbonization is completed, the particles are taken out to obtain cobalt carbide nanoparticles, which are then ground.

[0069] (5) Disperse 20 mg of cobalt carbide in 100 mL of deionized water and ultrasonicate for 2 h. Filter the cobalt carbide suspension onto a PTFE membrane at room temperature for 10 min.

[0070] Example 4

[0071] (1) Weigh 0.75 mmol of cobalt acetate and 0.5 mmol of potassium cobalt cyanide to prepare a solution, add 200 mL of deionized water to each solution, and stir to fully dissolve them.

[0072] (2) Add the prepared cobalt acetate solution dropwise into the potassium cobalt cyanide solution and continue stirring for 15 minutes after the addition.

[0073] (3) The obtained pink suspension was allowed to stand at room temperature for 48 h, and the obtained Co-PBA was centrifuged at 10,000 rpm for 4 min, washed twice with deionized water, then washed twice with anhydrous ethanol, dried at 80°C for 12 h, and then ground.

[0074] (4) Place the ground Co-PBA in H 2 :CO 2 =1:1 mixed reducing atmosphere, carbonization calcination is carried out at 250°C, the heat preservation time is 10h, and after carbonization is completed, the particles are taken out to obtain cobalt carbide nanoparticles, which are then ground.

[0075] (5) Disperse 20 mg of cobalt carbide in 100 mL of deionized water and ultrasonicate for 5 h. Filter the cobalt carbide suspension onto a PTFE membrane at room temperature for 30 min.

[0076] Experimental Example 1

[0077] Preparation of MXenes / PTFE:

[0078] (1) Add 20 mg of Mxenes powder into 100 mL of deionized water and treat with ultrasound for 2 h.

[0079] (2) Then, the Mxenes suspension was filtered onto the PTFE membrane under stirring for 10 min to obtain a Mxenes / PTFE membrane composite material for further use.

[0080] Photothermal conversion capability and interfacial water evaporation performance test:

[0081] The photothermal conversion capacity was tested at room temperature, with 20 mg of cobalt carbide and Mxenes reference powder placed in a sample tube. The test conditions were: the light source was a xenon lamp, the wavelength was simulated sunlight AM 1.5, and the light intensity was 0.2 W cm -2 , the irradiation time is 15min. Figure 5 As shown, from bottom to top are blank sample tube, Mxenes powder, Co prepared in Example 1 2 The photothermal conversion capacity of C powder is compared with that of Mxenes powder, Co 2 C nanoparticles exhibited higher photothermal conversion ability.

[0082] The photothermal water evaporation performance was tested in a photothermal water evaporation system. Specifically, a 100 mL beaker filled with water was placed on an electronic balance with an accuracy of 0.0001 g. 2 The C / PTFE film is placed on the upper surface of the beaker in contact with the water. The light source is placed just above the water evaporation system. The light intensity is kept constant during the test by adjusting the current and the photometer to assist in correction. Turn on the light source and evaluate the Co by detecting the mass change on the electronic balance. 2 C / PTFE film composite material was tested for its photothermal water evaporation performance. The test conditions were: the light source was a xenon lamp, the wavelength was simulated sunlight AM 1.5, and the light intensity was 0.1W·cm -2 , the irradiation time is 60min. Figure 6 As shown, from top to bottom are PTFE film, Mxenes / PTFE film, Co prepared in Example 1 2 C / PTFE film material photothermal water evaporation efficiency, compared with PTFE film, Mxenes / PTFE film, Co 2 C / PTFE film material exhibits higher photothermal effect and photothermal water evaporation efficiency.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanoscale Co2C / PTFE composite photothermal material, characterized in that: include: Using cobalt-based Prussian blue analog Co-PBA as a precursor, carbonization is carried out at 230-330°C for 5-15 h in a mixed reducing atmosphere of CO2 / H2 to obtain nano-scale cobalt carbide particles; dispersing the nano-scale cobalt carbide particles in a solvent to form a nano-scale cobalt carbide particle suspension; The nanoscale cobalt carbide particle suspension is filtered onto a polytetrafluoroethylene (PTFE) film to obtain a Co2C / PTFE film composite material; Among them, the volume ratio of H2 and CO2 is 1:1~1.5; The temperature of carbonization roasting is 230-330 °C and the time is 5-15 h; The preparation method of the cobalt-based Prussian blue analog Co-PBA comprises: Dissolving cobalt salt and potassium cobalt cyanide in water respectively to obtain a cobalt salt solution and a potassium cobalt cyanide solution; The cobalt salt solution and the potassium cobalt cyanide solution are mixed, allowed to stand, centrifuged, washed, dried, and ground to obtain Co-PBA.

2. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The dispersion is carried out by ultrasonic dispersion, and the treatment time is 1-5 h.

3. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The concentration of the nano-scale cobalt carbide particle suspension is 0.1-1.0 mg / ml.

4. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The filtration time is 5-60 min.

5. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The cobalt salt is one or more of cobalt nitrate, cobalt acetate and cobalt chloride.

6. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The molar ratio of the cobalt salt to potassium cobalt cyanide is 0.5-3:

1.

7. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The standing time is 0-96 h, and the standing temperature is room temperature.

8. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The centrifugal speed is 5000-10000 rpm and the centrifugal time is 5-10 min.

9. The method for preparing the nanoscale Co2C / PTFE composite photothermal material according to claim 1, characterized in that: The cleaning reagents are deionized water and ethanol; the drying temperature is 50-150 ℃, and the drying time is 2-48 h.

10. The cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material prepared by the method according to any one of claims 1 to 9.

11. Use of the cobalt carbide nanoparticle-loaded polytetrafluoroethylene film material according to claim 10 in photothermal water evaporation.

Citation Information

Patent Citations

  • Cobalt carbide based catalyst used for directly preparing olefin from synthesis gas, and preparation method and application thereof

    CN105772049A

  • Catalyst for preparing low-carbon mixed alcohol through carbon oxide hydrogenation and preparation method of catalyst

    CN106975486A